2019
DOI: 10.1090/jag/747
|View full text |Cite
|
Sign up to set email alerts
|

Parallel transport for vector bundles on 𝑝-adic varieties

Abstract: We develop a theory ofétale parallel transport for vector bundles with numerically flat reduction on a p-adic variety. This construction is compatible with natural operations on vector bundles, Galois equivariant and functorial with respect to morphisms of varieties. In particular, it provides a continuous p-adic representation of theétale fundamental group for every vector bundle with numerically flat reduction. The results in the present paper generalize previous work by the authors on curves. They can be se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Indeed, given any two choices of an exponential, the resulting equivalences on indecomposable objects only differ by twists with analytic torsion line bundles. Related work Towards establishing a p-adic Corlette-Simpson correspondence for representations of the étale fundamental group, Deninger and the third author have investigated the case of Higgs bundles with vanishing Higgs field, in which case they show that one can attach representations to vector bundles with numerically flat reduction [12,13]. Würthen [41] has extended this functor to the rigid analytic case and has shown that for analytic vector bundles, the notion of numerically flat reduction is closely related to being pro-finite-étale, i.e.…”
Section: Naturality Of the Correspondencementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, given any two choices of an exponential, the resulting equivalences on indecomposable objects only differ by twists with analytic torsion line bundles. Related work Towards establishing a p-adic Corlette-Simpson correspondence for representations of the étale fundamental group, Deninger and the third author have investigated the case of Higgs bundles with vanishing Higgs field, in which case they show that one can attach representations to vector bundles with numerically flat reduction [12,13]. Würthen [41] has extended this functor to the rigid analytic case and has shown that for analytic vector bundles, the notion of numerically flat reduction is closely related to being pro-finite-étale, i.e.…”
Section: Naturality Of the Correspondencementioning
confidence: 99%
“…Lemma 4. 13 Let K be any non-archimedean field over Q p and T a finite free Z pmodule. Consider V := T ⊗ Z p G a as a vector group.…”
Section: Proofmentioning
confidence: 99%
“…In the case of vanishing Higgs field, this question has been studied by Deninger-Werner [DW20] and Würthen [Wü20,§3], whose results suggest that in the special case of vanishing Higgs field, vector bundles that are trivialised by pro-finite-étale covers give the correct subcategory of Higgs bundles. We argued in [Heu20a,§4] that it is also the right condition in the case of rank one, and used it to construct the Simpson correspondence for line bundles.…”
Section: Geometrisation Of P-adic Simpson Correspondence In Rank Onementioning
confidence: 99%
“…A major open question in the field is which Higgs bundles correspond to representations: Deninger and the third author have investigated the case of numerically flat vector bundles with trival Higgs field in [DW05b] and [DW20]. Würthen [Wü20] has shown that for analytic vector bundles, the notion of numerical flatness is closely related to being pro-finite-étale.…”
Section: Introductionmentioning
confidence: 99%